Structural Insights into Dissimilatory Sulfite Reductases: Structure of Desulforubidin from Desulfomicrobium Norvegicum - Oliveira, Tania F.; Franklin, Edward; Afonso, José P.; Khan, Amir R.; Oldham, Neil J.; Pereira, Inês A. C.; Archer, Margarida (Frontiers in Microbiology, 2011)
Dissimilatory sulfite reductases (dSiRs) are crucial enzymes in bacterial sulfur-based energy metabolism, which are likely to have been present in some of the earliest life forms on Earth. Several classes of dSiRs have been proposed on the basis of different biochemical and spectroscopic properties, but it is not clear whether this corresponds to actual physiological or structural differences. Here, we describe the first structure of a dSiR from the desulforubidin class isolated from Desulfomicrobium norvegicum. The desulforubidin (Drub) structure is assembled as α2β2γ2, in which two DsrC proteins are bound to the core [DsrA]2[DsrB]2 unit, as reported for the desulfoviridin (Dvir) structure from Desulfovibrio vulgaris. Unlike Dvir, four sirohemes and eight [4Fe–4S] clusters are present in Drub. However, the structure indicates that only two of the Drub coupled siroheme-[4Fe–4S] cofactors are catalytically active. Mass spectrometry studies of purified Drub and Dvir show that both proteins present different oligomeric complex forms that bind two, one, or no DsrC proteins, providing an explanation for conflicting spectroscopic and biochemical results in the literature, and further indicating that DsrC is not a subunit of dSiR, but rather a protein with which it interacts.